Medical and Islamic perspectives on human immunodeficiency virus infection and its prevention - Abdullah, Fa’iza; Hashi, Abdurezak Abdulahi; Said, Abdul Hadi; Mat Nor, Mohd Basri (International Islamic University Malaysia, 2019)
Human Immunodeficiency Virus (HIV) that causes Acquired Immune Deficiency Syndrome (AIDS) is one of the world’s most serious health and nation-state destructions. It creates long-term economic and psychosocial impact on the lives of individuals, families and communities. Since the first reported case of HIV/AIDS in Malaysia in 1986, its prevalence has escalated significantly. As of December 2017, there are over 115,263 reported cases of HIV infections in the country and over 40,000 people died from HIV/AIDS1. Although many religious people regarded HIV infection as a divine punishment for their sins of sexual promiscuity, Islamic teaching emphasises the prevention of the disease and care for people living with HIV or AIDS. It is imperative to discuss the Islamic perspectives in providing ways to prevent the spread of HIV and support to people living with HIV (PLHIV). This article focuses on epidemiological data; highlight the burden of HIV infection/AIDS in Malaysia and its impact on the society, HIV infection from medical perspective and its preventive measures from Islamic viewpoints. A good teamwork among healthcare providers and religious leaders is compulsory as it may improve the preventive strategies to curb the disease in the country.